Construction and Characterization of Mutants of the TEM-1 β-Lactamase Containing Amino Acid Substitutions Associated with both Extended-Spectrum Resistance and Resistance to β-Lactamase Inhibitors - Stapleton, Paul D. (American Society for Microbiology, 1999)
Extended-spectrum TEM β-lactamases (ESBLs) do not usually confer resistance to β-lactamase inhibitors such as clavulanate or tazobactam. To investigate the compatibility of the two phenotypes we used site-directed mutagenesis of the bla(TEM-1) gene to introduce into the TEM-1 β-lactamase amino acid substitutions that confer the ESBL phenotype: TEM-12 (Arg164→Ser), TEM-26 (Arg164→Ser plus Glu104→Lys), TEM-19 (Gly238→Ser), and TEM-15 (Gly238→Ser plus Glu104→Lys). These were combined with three sets of substitutions that confer inhibitor resistance: TEM-31 (Arg244→Cys), TEM-33 (Met69→Leu), and TEM-35 (Met69→Leu and Asn276→Asp). Introduction of the Arg244→Cys substitution gave rise to inhibitor-resistant hybrid enzymes that either lost ESBL activity (TEM-12, TEM-15, and TEM-19) or had reduced activity (TEM-26) against ceftazidime. In contrast, the introduction of Met69→Leu or Met69→Leu plus Asn276→Asp substitutions did not significantly affect the abilities of the enzymes to confer resistance to ceftazidime, although increased susceptibility to cefotaxime was observed with Escherichia coli strains that expressed the TEM-19 and TEM-26 β-lactamases. With the exception of the TEM-12 β-lactamase, introduction of the Met69→Leu substitution did not give rise to enzymes with increased resistance to clavulanate compared to that of the TEM-1 β-lactamase. However, introduction of the double substitution Met69→Leu plus Asn276→Asp in the ESBLs did give rise to low-level (TEM-19, TEM-15, and TEM-26) or moderate-level (TEM-12) clavulanate resistance. None of the hybrid enzymes were as resistant to clavulanate as the corresponding inhibitor-resistant TEM β-lactamase mutant, suggesting that active-site configuration in the ESBLs limits the degree of clavulanate resistance conferred.